2003
DOI: 10.1163/156853803763806902
|View full text |Cite
|
Sign up to set email alerts
|

Life history of a small form of the plethodontid salamander Desmognathus quadramaculatus

Abstract: Abstract. We sampled Desmognathus quadramaculatus, one of the largest species of plethodontid salamanders in eastern North America, from a population exhibiting extremely small adult body sizes in the Bald Mountains of North Carolina (USA). In order to test the hypothesis that miniaturization in desmognathine salamanders is due to early metamorphosis and maturation, we estimated ages and sizes at metamorphosis and maturation. Analysis of size-frequency distributions suggests that most larvae metamorphose after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Similarly, within Desmognathus, competition and intraguild predation seem to have driven body-size diversification, patterns of microhabitat use, and the assembly of communities comprised of different-sized species (Hairston 1986;Kozak et al 2005). Although less is known about the relationship between body-size variation and ecological interactions among species of spelerpines, the available data suggest that body-size differences also mitigate competitive and predatory interactions (Beachy 1994(Beachy , 1997Bruce 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, within Desmognathus, competition and intraguild predation seem to have driven body-size diversification, patterns of microhabitat use, and the assembly of communities comprised of different-sized species (Hairston 1986;Kozak et al 2005). Although less is known about the relationship between body-size variation and ecological interactions among species of spelerpines, the available data suggest that body-size differences also mitigate competitive and predatory interactions (Beachy 1994(Beachy , 1997Bruce 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained data on local species composition from eight intensively studied sites across the southern Appalachians (Fig 2; Table 1). Data on species that co‐occur on the same study plots were gathered during field collections by KHK (this study) and obtained from the literature (Organ 1961; Smith and Petranka 2000; Petranka and Murray 2001; Beachy and Bruce 2003; Petranka and Smith 2005; J. W. Petranka, pers. comm.).…”
Section: Methodsmentioning
confidence: 99%
“…The long larval period has been associated with several other life-history attributes, including large genome size (Sessions and Larson 1987), long generation times (Hairston 1987), low metabolic scope (Feder 1983), and delayed maturation (Beachy 1995a; Ryan and Bruce 2000; Beachy and Bruce 2003). In any case, the longest larval periods in plethodontids covary with delays in maturation age and consequent large adult body size (Bruce 2016a).…”
Section: How Is the Larval Life History Different In Plethodontids?mentioning
confidence: 99%
“…Therefore, metamorphic timing or size may not necessarily be optimized in ways predicted by theory (Wilbur and Collins, 1973; Werner, 1986; Alford, 1999; Harris, 1999; Day and Rowe, 2002). For example, there is significant within-species geographic variation in metamorphic age and size in the desmognathan salamanders (e.g., Bruce, 1972, 1988; Camp et al, 2000), but demographic comparisons and theoretical considerations indicate that age at maturation or egg size are likely to be the primary targets of selection rather than metamorphosis (Tilley, 1980; Bernardo, 1994; Beachy, 1995; Beachy and Bruce, 2003). Therefore, variation in metamorphic size or timing or both may simply be a correlate of these variables, i.e., egg size and maturation age (Bernardo, 1994; Beachy, 1995).…”
mentioning
confidence: 99%
“…Furthermore, Whiteman (1997) suggested that facultatively paedomorphic salamanders have sex-specific differences in fitness that result in between-sex variation in expression of paedomorphosis. Females have larger commitment to gonads than males because eggs are energetically more demanding to produce (e.g., they contain yolk), and male salamanders generally mate at earlier ages (e.g., Tilley, 1980; Bruce, 1988; Whiteman, 1997; Ryan and Bruce, 2000; Beachy and Bruce, 2003). This sex difference, when combined with the influence of growth on development, means that the sex-specific expression of paedomorphosis is complex (Denoël et al, 2005).…”
mentioning
confidence: 99%